Membangun Kepedulian Lingkungan Warga Kelurahan Bajak Melalui Bank Sampah - Fachrul Rozi Ramadhan; Teresa Aulia Putri; Cindy Andira; Sabrina Bernoza Hanifah; M. Farid Adrian; Rizkika Amelia Putri; Hafidz Rizkian Akbar; Muhammad Fauzan Aziman (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Waste management remains a serious issue in Bajak, Bengkulu City, due to the common practice of burning or burying household waste without prior sorting. Through the Community Service Program (KKN), students from the University of Bengkulu initiated a community-based “Bank Sampah” or waste bank from scratch as a solution to increase public awareness and participation in household waste management. This program was implemented using a descriptive qualitative method with participatory and educational approaches, involving local residents in all stages of the activity from socialization, waste sorting, and collection, to recording waste deposits. Sorted inorganic waste was weighed and converted into monetary value as a form of incentive. The results showed positive behavioral changes, improved environmental awareness, and the development of collective responsibility among residents. Despite facing technical limitations, the program ran effectively and has strong potential to serve as a model for community-based, environmentally friendly, and sustainable waste management.